In Vitro Interaction between Venous Blood Clots and Radiopharmaceuticals - Kempi, V.; Persson, B. R. R. (Nuklearmedizin - NuclearMedicine, 1985)
Clots of 1 ml venous blood formed in glass tubes after 10 min at room temperature were incubated at 37° C with the radiopharmaceutical to be studied. Methods for quality control of the radiopharmaceuticals were compared. Gel chromatography scanning was found to give reliable information. The incorporation into the clot was studie’d at different pH values and after various time intervals. The highest incorporation was found for 125I-fibrinogen and for 99mTc-mac-roaggregates of albumin, followed by 99mTc-sulphur colloid and 99mTc-strep-tokinase at pH less than 2. The titrated initial dose of 99mTc-streptoki-nase was studied at various pH levels. The lysing effect was less in the pH range 1-2.5, where the best labeling yield was obtained. The inactivation of streptokinase by the labeling procedure was also studied with im-munoelectrophoresis and decomposition of casein. In vitro studies of the interaction of radiopharmaceuticals with clots add information for the clinical use of radiopharmaceuticals for thrombus localization.